Association of Estrogen Receptor TA Repeats with Endometrial and Ovarian Cancers in Basrah Province - Abd Al-wahid, Zeena H.; Ayoob, Anwar N.; Al-Badran, Adnan I.; Abood, Rafid A. (Asian Pacific Journal of Cancer Biology, 2025)
Background: Ovarian and endometrial malignancies are complex diseases, since a defect in hormone balance can be the most important cause of tumor formation. Aim of study: Examine and identify the association between ER TA repeats with endometrial and ovarian cancers in Basrah women. Patients: Groups include 50 healthy controls and 50 cancer patients, divided into 20 endometrial cancer patients and 30 ovarian cancer patients. Results and Discussion: The result shows TA 11–12 repeats are the most common in endometrial cancer in 68% of cancer patients, followed by TA≥10 in 8% and 4% for both 13–14 repeats and ≤15, whereas TA repeats 11–12 and ≤15 repeats are the most common in ovarian cancer in 22% for each one, followed by ≥10 TA in 10% and 13–14 in 6%. The control groups have four groups of repeat numbers: 11–12 TA repeat in 68%, 13–14 in 20%, ≤15in 10%, and ≥10 in 2%. Simultaneously, a substantial association exists between the two types of cancers and the TA repeat length variation of the estrogen receptor type alpha. Conclusion: The length of the TA repeat in estrogen receptor alpha has a significant risk for ovarian and endometrial cancer.